Analysis on Spatio-temporal Change Characteristics of Extreme Precipitation in Hainan Island - ZHANG Shuqi; XIAO Jing (Renmin Zhujiang)
The spatio-temporal variation characteristics and future trends of extreme precipitation in Hainan Island are analyzed based on 9 extreme precipitation indices from 188 rainfall stations in Hainan Island from 1980 to 2022, by means of methods such as linear regression, moving average, cumulative anomaly method, Mann-Kendall test, sliding T-test, Lee-Heghinian test, R/S analysis method. Then mutation analysis on the extreme precipitation index sequence is performed. The results show that: ① The spatial distribution of extreme precipitation events in Hainan Island is "more in the east and less in the west"; the eastern part has more precipitation and is more prone to rainstorms, and Jianfengling in the western part is also more likely to have short-term heavy rainfall. ② In the past 43 years, the entire island has been tending towards humidification, with short-term precipitation on the 1st and 3rd day increasing in the north and west, and decreasing in the south; consecutive wet days (CWD) increase, consecutive dry days (CDD) decreases, and the trend of rainstorms and heavy rainstorms increases in eastern, northern and western coastal areas. ③ Extreme precipitation indices PRCPTOT, Rx1day, Rx3day, and R99PTOT show an insignificant increase at rates of 45.57, 1.62, 6.08, and 2.80 mm/10a, respectively; among the extreme precipitation day indices, CDD significantly decreases at a rate of 2.07 d/10a, while CWD, R50, and R100 show an insignificant increase at 0.26, 0.22, and 0.02 d/10a, respectively; the extreme precipitation intensity index SDII show an insignificant decrease at 0.18 (mm/d)/10a. ④ In the future, CDD and SDII will continue to increase with strong persistence, and PRCPTOT, Rx1day, Rx3day, R99PTOT, CWD, R50, and R100 will continue to decrease with weak persistence. ⑤ Mutation test shows that mutations in PRCPTOT, Rx1day, Rx3day, R99PTOT, R50, and R100 occurred around 2007, the SDII mutation point appeared in 1988, and the CWD and CDD mutation points appeared around 1995 and 2010, respectively. These results can provide a reference for rainstorm disaster prevention in Hainan Island.